Microstructure and Magnetic Properties of M-Type Sr0.1Ca0.4La0.5Fe12O19 Ferrites: The Impact of Different Precursors - Xiubin Zhao; Shuang Zhang; Jinsong Li; Ailin Xia; Yujie Yang (Magnetochemistry, 2022)
M-type Sr0.1Ca0.4La0.5Fe12O19 powder specimens doped with different precursors RFe2O4(R = Co, Ni, Cu, Zn, and Mg) were prepared via a traditional solid-state reaction method. The structural and magnetic properties of the specimens were studied. Only nthe single magnetoplumbite phase was found in all the specimens with uniformly distributed particles. The specimen with Zn-type precursor has the highest saturation (Ms), while the specimen with Co-type precursor has the highest remanent magnetism (Mr), coercivity (Hc), and the best comprehensive magnetic properties.